Root gravitropism: quantification, challenges, and solutions - Muller, Lukas; Bennett, Malcolm J.; French, Andy; Wells, Darren M.; Swarup, Ranjan (Springer Verlag, 2018)
Better understanding of root traits such as root angle and root gravitropism will be crucial for development of crops with improved resource use efficiency. This paper describes a high-throughput, automated image analysis method to trace Arabidopsis (Arabidopsis thaliana) seedling roots grown on agar plates. The method combines a ‘particle-filtering algorithm with a graph-based method’ to trace the centre line of a root and can be adopted for the analysis of several root parameters such as length, curvature, and stimulus from original root traces.